2018
DOI: 10.3390/educsci8040202
|View full text |Cite
|
Sign up to set email alerts
|

The Mathematics Teacher Exchange and ‘Mastery’ in England: The Evidence for the Efficacy of Component Practices

Abstract: ‘Mastery’ is central to current policy in mathematics education in England, influenced by East Asian success in transnational assessments. We scrutinise the prospects for mastery pedagogies to improve pupil attainment in English primary schools. The Mathematics Teacher Exchange (MTE)—an element of the mastery innovation—involves teachers visiting Shanghai and then hosting Shanghai teachers in their schools. Informed by programme evaluation, core component practices are analysed, which were implemented by schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 69 publications
0
45
0
Order By: Relevance
“…A notable difference, and one pointed to by teachers, between, for example, Shanghai primary mathematics pedagogy and English practice relates to the amount of content addressed in a single lesson. Teachers adopting mastery approaches report a slowing down of the speed at which the curriculum is taught (Boylan et al 2019). However, "teaching for mastery" continues to emphasise progressing through the curriculum in a predetermined way, albeit more slowly (and ideally together and with greater depth than common English primary mathematics education practice).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A notable difference, and one pointed to by teachers, between, for example, Shanghai primary mathematics pedagogy and English practice relates to the amount of content addressed in a single lesson. Teachers adopting mastery approaches report a slowing down of the speed at which the curriculum is taught (Boylan et al 2019). However, "teaching for mastery" continues to emphasise progressing through the curriculum in a predetermined way, albeit more slowly (and ideally together and with greater depth than common English primary mathematics education practice).…”
Section: Resultsmentioning
confidence: 99%
“…The idea of pace has been a key influence on primary mathematics education and continues to be so in spite of the discontinuation of the National Strategies organisational framework and recent moves to adopt a "mastery" approach to learning (Boylan et al 2019). Until very recently, the inspection regime in England focused not only on monitoring progress over time but on observing progress in single lessons (Ofsted 2015), often a twenty minute episode within a lesson, thus influencing school leaders' and teachers' beliefs about what is desirable -and therefore what is desired.…”
Section: Regulated Timementioning
confidence: 99%
“…This has proven difficult, in part due to the wide range of different assessments available. Study 1 (Chapter 4) showed no difference between a programming game and phonics activities on story sequencing ability, supporting the results of much larger studies measuring CT improvements after a Scratch curriculum (Straw et al, 2017) and mathematics improvements after a Scratch curriculum (with CT as a secondary measure) (Boylan et al, 2018).…”
Section: Computational Thinkingmentioning
confidence: 56%
“…Examples include the Bebras Computing Challenge (Dagiene & Futschek, 2008) and the Computational Thinking Pattern Quiz (Basawapatna et al, 2011). Bebras has been used recently as a measure of CT in two large educational studies (Boylan et al, 2018;Straw et al, 2017), so will be discussed in more detail.…”
Section: Skill-transfer Measuresmentioning
confidence: 99%
See 1 more Smart Citation